2023
DOI: 10.1037/emo0001186
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of extrinsic emotion regulation strategies in text-based online communication.

Abstract: In daily life, others play a key role in helping regulate an individual's emotions. Such emotion regulation occurs not only in face-to-face communication but also in text-based online communication. To date, much research has examined strategies for alleviating one's own negative emotions (intrinsic emotion regulation) based on the process model of emotion regulation (Gross, 1998(Gross, , 2015a. However, little is known about the effectiveness of the full range of strategies for alleviating others' negative em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…The letters from the participants were coded for the type of EER strategies used, as outlined in Nozaki & Mikolajczak (2022). Besides Nozaki's strategies of reappraisal, problemsolving and empathic responding, we included acceptance.…”
Section: Codingmentioning
confidence: 99%
See 2 more Smart Citations
“…The letters from the participants were coded for the type of EER strategies used, as outlined in Nozaki & Mikolajczak (2022). Besides Nozaki's strategies of reappraisal, problemsolving and empathic responding, we included acceptance.…”
Section: Codingmentioning
confidence: 99%
“…These studies are based on the idea that people use multiple emotion regulation strategies simultaneously to regulate others' emotions, which is known as polyregulation. For example, in a study by Nozaki & Mikolajczak (2022), participants wrote letters to recipients who had recently gone through a negative emotional experience. These letters were rated by independent coders and identified six main EER strategies: problem-solving, distraction, reappraisal, suppression, relaxation, and empathic responding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this research is still in its infancy, it suggests that EER may reduce physiological stress responses, especially sympathetic-related arousal ( Inagaki and Eisenberger, 2016 ). A recent study that used text-based online communication has demonstrated that EER is most effective when people use emotion regulation strategies such as cognitive reappraisal and problem-solving, as well as when providing empathic responses ( Nozaki and Mikolajczak, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that extrinsic IER significantly correlates with individual differences and results in positive implications for social relationships. 14,[25][26][27][28][29] To test the convergent validity of the EERMS, we investigated the associations of the motives of extrinsic IER with several well-being indicators (moral self-identity, peer relationships, and perceived social support). Moral identity has been described as the degree to which one holds moral concerns as important to one's identity.…”
Section: Introductionmentioning
confidence: 99%